2018
DOI: 10.1108/ilt-05-2017-0143
|View full text |Cite
|
Sign up to set email alerts
|

Study on the tribological behaviors of copper nanoparticles in three kinds of commercially available lubricants

Abstract: Purpose The purpose of this paper is to study the tribological properties of Cu nanoparticles (NPs) as lubricant additives in three kinds of commercially available lubricants. Design/methodology/approach A four-ball machine is used to estimate the tribological properties of Cu NPs as lubricant additives in three kinds of commercially available lubricants. Three-dimensional optical profiler and electrical contact resistance are evaluated to investigate the morphology of the worn surfaces and the influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 33 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…It has been reported that when copper nanoparticles are employed as an additive in SAE 5w-40 oil at an optimum concentration of 0.8 wt%, the resulting COF is reduced by almost 13% when tests are conducted on a four-ball tribotester. In same study, Cu nanoparticles were also used as additives in SAE 5w-20 oil, and it was found that when 1.6 wt% of Cu nanoparticles were added, the COF was reduced by 28.5% [ 45 ]. It has also been reported that the COF of the lubricant oil SAE 40 is improved by a factor of 14% when Cu nanoparticles at an optimum concentration of 0.01 vol% are used in a four-ball tribotester [ 38 ].…”
Section: Nanoparticles In Synthetic Lubricantsmentioning
confidence: 99%
“…It has been reported that when copper nanoparticles are employed as an additive in SAE 5w-40 oil at an optimum concentration of 0.8 wt%, the resulting COF is reduced by almost 13% when tests are conducted on a four-ball tribotester. In same study, Cu nanoparticles were also used as additives in SAE 5w-20 oil, and it was found that when 1.6 wt% of Cu nanoparticles were added, the COF was reduced by 28.5% [ 45 ]. It has also been reported that the COF of the lubricant oil SAE 40 is improved by a factor of 14% when Cu nanoparticles at an optimum concentration of 0.01 vol% are used in a four-ball tribotester [ 38 ].…”
Section: Nanoparticles In Synthetic Lubricantsmentioning
confidence: 99%
“…Metallic NPs have unique chemical and physical properties as lubricant additives [59][60][61][62][63][64][65][66][67][68][69][70][71]. Nano-metals with low shear stress, high extension, and low melting point have been used as FMs owing to their excellent friction-reducing, anti-wear, and self-repairing ability.…”
Section: Metalsmentioning
confidence: 99%
“…Nano-metals with low shear stress, high extension, and low melting point have been used as FMs owing to their excellent friction-reducing, anti-wear, and self-repairing ability. Among metallic NPs, Cu-containing nanolubricants have received particular attention owing to their remarkable properties [59][60][61][62][63][64][65][66][67][68][69][70][71]. Copper NPs usually have small particle size, low melting point, and the desired ductility; therefore, they are well perceived as an excellent AW and EP agent in comparison with similar products [72,73].…”
Section: Metalsmentioning
confidence: 99%
“…In recent years, the use of nanomaterials as lubricant additives has become an important research area due to their potential excellent anti-wear and friction-reducing in tribology [1][2][3][4][5][6][7][8][9]. Along with soaring of environmental concern for lubricating oil products and enforcement of more strict environmental protection laws, the demand for green lubricating oil additives rises [10].…”
Section: Introductionmentioning
confidence: 99%